DEVELOPMENT OF PHYSICS LEARNING MEDIA USING ANDROID BASED AUGMENTED REALITY IN STATIC ELECTRICAL MATERIALS FOR HIGH SCHOOL STUDENTS - Badryatusyahryah Badryatusyahryah; Imas Ratna Ermawati; Mirzanur Hidayat (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2020)
This study aimed to develop physics learning media using Android-based Augmented Reality on static electricity topic in the form of an application called PARE (Physics AR Education). This application focuses on visualizing static electricity topic. The method used in this study is Research-and-Development. This study was conducted in three schools including SMAN 12 Tangerang, SMAN 90 Jakarta, dan SMAN 63 Jakarta each in two-class respondents. Validation tests were conducted by material and media experts. Media assessment shows that all the 15 statements received an average score of 4,49 hence categorized as very good. The material assessment shows that all the 12 statements received an average score of 4,07 hence categorized as good. The whole percentage of expert assessment reached 85,6%. Students' trial tests were conducted twice including small-scale and large-scale trial tests. The small-scale trial test was conducted towards 13 students and received an average score of 4,39 hence categorized as very good. Meanwhile, the large-scale trial test towards 201 students received an average score of 4,01 hence categorized as good. The whole percentage of the trial test reached 84%. Overall, media effectivity could be seen based on pretest and posttest that were conducted in SMA Negeri 12 Tangerang, SMAN 90 Jakarta, and SMAN 63 Jakarta with a total of 201 students and showed that the percentage reached 96,87% which categorized as very good.